Rational pharmacotherapy of arterial hypertension in real clinical practice: diuretics through drug safety - Dmitry I. Trukhan; Natalya V. Bagisheva (LLC "MEDIAFORMAT", 2023)
The use of diuretics in arterial hypertension is pathogenetically justified, which is due to the significant role of an increase in the volume of circulating blood and the retention of sodium ions in the internal environment of the body, in increasing blood pressure. In clinical guidelines, the choice of a diuretic for the treatment of hypertension is limited to 3 drugs: hydrochlorothiazide, chlorthalidone and indapamide. Thiazide and thiazide-like diuretics are often combined into a single group of "thiazides", however, they have significant differences in the mechanism of their action, clinical effects, drug safety profile, partly in the parameters of the effectiveness of blood pressure control, as well as the evidence base in randomized clinical trials. In the first part of the review, along with evidence of the effectiveness of the use of diuretics in arterial hypertension, various aspects of the drug safety of drugs in this group are considered, both possible metabolic disorders and more rare, but possible disorders of the organ of vision, skin adverse reactions and the risk of acute respiratory distress. -syndrome. The second part of the review considers the efficacy and safety of the thiazide-like diuretic indapamide.